The Abbreviated 3-Item Versions of the Satisfaction With Life Scale and the Satisfaction With Love Life Scale - Neto, Joana Sequeira (2024)
The Satisfaction with Life Scale (SWLS) and the Satisfaction with Love Life Scale (SWLLS) are cognitive measures of subjective well-being. Each scale includes 5 items. The major goals of this work were to analyze the psychometric features and validity of the abbreviated 3-item forms of the Satisfaction with Life Scale (SWLS-3) and the Satisfaction with Love Life Scale (SWLLS-3), as well as the measurement invariance (MI) by gender and age in a Portuguese population. The sample comprised 1,271 participants with an average age of 38 years. Confirmatory factor analyses (CFA) demonstrated that the two-dimensional model of SWLS-3 and of SWLLS-3 presented good fit indices. The reliability was adequate. Furthermore, these scales demonstrated MI across gender and age. The correlations of the 3- and 5-item measures with these well-being measures were very similar. Overall, the 3-item versions of the SWLS-3 and the SWLLS-3 are presented as valid and reliable measurement tools.